KINETIC TYPOGRAPHY IN PROFESSIONAL AND USER CONTENT OF DIGITAL MEDIA - Yenchev, Mykhailo (Theory and practice of design, 2025)
The purpose of the article is to identify the features of the formation and development of kinetic typography in the context of media evolution, as well as to conceptualize the practice of its use in modern digital media using the example of professional and user content. Methodology. The study uses the method of theoretical analysis; the typological method, thanks to which the main characteristics of kinetic typography were clarified; the historical and cultural method, the application of which is due to the importance of considering the formation of kinetic typography in historical retrospect; comparative analysis method, which contributed to the identification of the features of the use of kinetic typography in various types of visual content of digital media; method of art history and compositional analysis, etc. Results. According to the results of the study, it was found that kinetic typography can be considered as a representation of information using text in motion over a certain period of time, a form capable of conveying emotions through dynamic visualization of the text. Due to its ability, kinetic typography enhances the communicative properties of the text, itself becoming a catalyst for expressive power. Summarizing the theoretical materials presented in the scientific literature and based on the analysis of modern content of digital media, the following typology of kinetic typography can be proposed: by type of content (professional and user); by type of audiovisual forms (kinetic typography for feature films, television series, TV programs, trailers, spoilers, advertising videos, music videos, small screen forms of social media (short videos – Instagram Reels, YouTube Shorts, TikTok Story, etc.); by type of movement («sequential» or «serial presentation» and «dynamic presentation» (divided into global and local). Scientific novelty. For the first time, kinetic typography of professional and user content of digital media is considered from an art historical perspective. The author’s definition of the concept of «kinetic typography» and typology are proposed. Unknown and little-known art historical works of foreign researchers related to the issue of kinetic typography in new media are introduced into scientific circulation. Practical relevance. The results of the study of the process of development of kinetic typography in the context of media evolution and in modern stage, through the prism of the specifics of professional and user content of digital media can become the basis for further art-historical research of the indicated issues. Individual provisions can be used when writing manuals and included in courses of lectures on graphic design.